Spatial characteristics of human resources in the context of innovation- and imitation-based economies - Csugány, Julianna; Tánczos, Tamás (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
Technological progress is a dynamic process that, via the application and the widespread use of new technologies, becomes the engine of growth through the achievement of efficiency gains in productivity. Most countries are unable to create new technologies because they do not have the appropriate resources or their institutional environment does not favour to innovation. However, technological progress can also be observed in these countries, by adapting new technologies developed and applied effectively elsewhere. Thus, technological progress can be achieved through independent research and development activities, that is, an innovation-driven way, and through the adaptation of new technologies which are already in use in other countries, i.e. in an imitation-driven way. Human capital is also essential for the creation and adaptation of technology, so the quantitative and qualitative features of the human resources available in a country determine the conditions of technological progress. Our research aims to illustrate spatial characteristics of human resources conditions by the method of spatial autocorrelation highlighted the differences between innovation-based and imitation-based economies.
Keywords: technological progress; spatial characteristics of human resources; innovation-based economics; imitation-based economics